28-Way vertebrate alignment and conservation track in the UCSC Genome Browser - Miller, Webb; Rosenbloom, Kate; Hardison, Ross C.; Hou, Minmei; Taylor, James; Raney, Brian; Burhans, Richard; King, David C.; Baertsch, Robert; Blankenberg, Daniel; Kosakovsky Pond, Sergei L.; Nekrutenko, Anton; et al. (Genome Research, 2007)
This article describes a set of alignments of 28 vertebrate genome sequences that is provided by the UCSC Genome Browser. The alignments can be viewed on the Human Genome Browser (March 2006 assembly) at http://genome.ucsc.edu, downloaded in bulk by anonymous FTP from http://hgdownload.cse.ucsc.edu/goldenPath/hg18/multiz28way, or analyzed with the Galaxy server at http://g2.bx.psu.edu. This article illustrates the power of this resource for exploring vertebrate and mammalian evolution, using three examples. First, we present several vignettes involving insertions and deletions within protein-coding regions, including a look at some human-specific indels. Then we study the extent to which start codons and stop codons in the human sequence are conserved in other species, showing that start codons are in general more poorly conserved than stop codons. Finally, an investigation of the phylogenetic depth of conservation for several classes of functional elements in the human genome reveals striking differences in the rates and modes of decay in alignability. Each functional class has a distinctive period of stringent constraint, followed by decays that allow (for the case of regulatory regions) or reject (for coding regions and ultraconserved elements) insertions and deletions.
10.1101/gr.6761107